2004
DOI: 10.1038/sj.hdy.6800455
|View full text |Cite
|
Sign up to set email alerts
|

Autosomal differences between males and females in hybrid zones: a first report from Barbus barbus and Barbus meridionalis (Cyprinidae)

Abstract: International audienceNarrow hybrid zones are generally subjected to the action of two forces: dispersal, which tends to homogenise the hybridising taxa, and selection against hybrids, which, in contrast, produces steep clines of introgression for diagnostic markers. Although differences between sexes in dispersal abilities or in susceptibility to hybrid counterselection are common in hybrid zones, autosomal genetic differences between males and females have never been reported to our knowledge. Barbus barbus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…On another hand, in the Caima zone, all backcross hybrids were in the direction of A. oligolepis , whereas mtDNA of both species was found in virtually the same proportions among A. oligolepis / A. oligolepis ‐like and P. duriense / P. duriense ‐like individuals. In general, these asymmetries in hybrid zones are considered to be the consequences of intrinsic attributes of the whole species that rarely or never depend on the geographical set‐up such as partial hybrid sterility, biased survival of hybrids (Chenouil et al. , 2004) or biased assortative mating and sexual selection (Meyer et al.…”
Section: Discussionmentioning
confidence: 99%
“…On another hand, in the Caima zone, all backcross hybrids were in the direction of A. oligolepis , whereas mtDNA of both species was found in virtually the same proportions among A. oligolepis / A. oligolepis ‐like and P. duriense / P. duriense ‐like individuals. In general, these asymmetries in hybrid zones are considered to be the consequences of intrinsic attributes of the whole species that rarely or never depend on the geographical set‐up such as partial hybrid sterility, biased survival of hybrids (Chenouil et al. , 2004) or biased assortative mating and sexual selection (Meyer et al.…”
Section: Discussionmentioning
confidence: 99%
“…The observed genetic differentiation between males and females was unexpected given that males and females are from the same cohorts and share genealogies within the pedigrees: their autosomal markers are mixed at each generation. Therefore, long-term evolutionary forces such as genetic drift or mutation could not generate autosomal genetic difference between sexes [29]. Moreover, selective effects were rarely (4/101, 3.97%) detected in the autosomal microsatellites.…”
Section: Discussionmentioning
confidence: 99%
“…The significant positive F IS observed in males is consistent with this argument as well. Alternative explanations for the sex-specific genetic differentiation would be differential viability, lifespan or hatching rate between sexes, which can lead to the allele frequency difference between females and males detected by F ST (see [8,29]). Unfortunately, given the available data in the Siberian jays, ascertaining the assumptions and quantifying the relevant parameters underlying these non-mutually exclusive hypotheses is difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also indicated a preponderance of the larger species acting as the maternal donor (Chenuil et al, 2004;Lajbner et al, 2009;Meraner et al, 2013).…”
Section: Natural Hybridization and Human-mediated Gene Flowmentioning
confidence: 93%